Event sponsorship and fundraising : an advanced guide - Lunt, Tom; Nicotra, Eva (London ; New York : Kogan Page Limited, 2019)
"Securing sponsorship and other sources of funding for events is becoming increasingly competitive, making differentiation and delivery vital. Event Sponsorship and Fundraising explores this complex area of event management, drawing on both experiential marketing and consumer behaviour theories, and developing critical insights on the dynamics of successful event sponsorship. Its coverage includes professional guidance on prospecting for sponsors, brand activation and evaluation, as well as advice on relationship management, proposal writing and pitching to potential sponsors. Event Sponsorship and Fundraising places each of these concepts at the heart of the Integrated Marketing Communications Mix, alongside cutting edge literature on the topic. Written by two highly experienced industry practitioners, both of which now teach on two of the UK's leading event management degree courses, and supported by a comprehensive set of online resources, this book is an invaluable go-to resource for event management students, tutors and professionals alike"--
Introduction to event sponsorship, fundraising, partnerships and relationship development -- Event sponsorship at the centre of the integrated marketing communications mix -- Delivering event sponsorship campaigns -- Identifying and securing sponsors and funding opportunities -- Prospecting for grant funding and sponsorship: case studies from Scottish cycling events -- Preparing and delivering a sponsorship pitch -- Managing relationships with sponsors and funding bodies -- Legal issues in event sponsorship and fundraising -- Evaluating sponsorship and grant-making relationships -- Where next for event sponsorship and fundraising? -- Practical templates to kick-start your event sponsorship and fundraising -- Afterword: building your career in sponsorship and fundraising.
Includes bibliographical references and index.
Keywords: Special events -- Management; Special events -- Marketing; Corporate sponsorship